Comparación de dos métodos de cosecha y transporte en el cultivo de banano (Musa spp), variedad cavendish en el cantón Buena Fe - Weisson Mendoza, Alejandro Ernesto (2013)
Being the banana combines one of the most important within the Ecuadorian economy much the activities of quality control and one of the ways of increasing production is decreasing damage in clusters thus avoiding the depletion of the fruit in the processing at the plant. For this reason arose to make the comparison of two methods of harvesting and transport in banana cultivation variety Cavendish in the canton Buena Fé for which Bertha Maria is chose hacienda owned by the Mendoza, objectives that were raised were: determine whether there are differences in quality in the fruit when harvested with ladder - condor and loincloth – wedge compare the performance of the crop with the methodology of cot-nursing versus condor, to assess which of the methods is higher costs. The treatments under study were the method of ladder - condor and loincloth - cradle, with 10 replications, was used a design completely at random (DCA), the evaluated variables were given by: weight (kg) cluster, number of hands per bunch, decline by mechanical damage (%), defects by selection and packaging, ratio and total costs. The treatments had no significant statistical differences in the variables bunch weight (kg), bunch weight after loss, number of hands, ratio, for the decrease by mechanical damage, the staircase treatment - condor presented the highest percentage with 23.49%; within the defects by selection and packing treatment loincloth - wedge reported the largest number of defects. The higher costs were recorded in the treatment escalera-condor with 14.07 USD.